Assessment of heat pumping technology in oleochemical fatty acid fractionation - N. M., Sidek; Mohamad Rizza, Othman (Universiti Malaysia Pahang, 2019)
Similar to petroleum industry, major energy consumption in oleochemical plants is also dominated by separation process in order to obtain purified oleochemical cuts. Combination of the distillation column with heat pumping system has emerged as one of the most popular techniques in heat integration. Although heat pumping technology has been proven to be effective in petroleum separation, the research on this technology in oleochemical separation has not yet been discovered. Hence, it would be appealing to investigate the feasibility of integrating heat pump technology with distillation units in hopes of reducing energy usage in the separation of oleochemical products. In this study, two configurations of heat pumping system, namely direct vapor recompression (VRC) and bottom flashing heat pump (BFHP) are simulated in Aspen Plus particularly for fractionation of palm kernel oil (PKO) fatty acid. Proper selection of thermodynamic package is discussed in detail. Only three major components of PKO-based fatty acid are involved in the simulation in order to arrive at simple simulation and easy convergence. Simulation results indicates that both configurations of heat pump can be feasibly integrated with the distillation column. However, to satisfy the heating and cooling requirement, supply of makeup utility is necessary.